2002
DOI: 10.1016/s0896-6273(02)00666-9
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Mechanisms Control the Timing of bHLH Function and Regulate Retinal Cell Fate

Abstract: During central nervous system development, neurons are often born in a precise temporal sequence. Basic helix-loop-helix (bHLH) transcription factors are required for the development of specific subpopulations of neurons, but how they contribute to their ordered genesis is unclear. We show that the ability of bHLH factors to regulate the development of distinct neuronal subtypes in the Xenopus retina depends upon the timing of their function. In addition, we find that the timing of bHLH function can be regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
110
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 53 publications
(6 reference statements)
5
110
0
Order By: Relevance
“…(Carl, et al, 2002, Mathers and Jamrich, 2000, Porter, et al, 1997 The bHLH (basic Helix Loop Helix) gene family of transcription factors also has pivotal roles in the unique patterning of transcription factors that guide retinal development (Mash1, Math3, Ngn2). (Akagi, et al, 2004, Brown, et al, 1998, Brown, et al, 2001, Hojo, et al, 2000, Kanekar, et al, 1997, Marquardt and Gruss, 2002, Moore, et al, 2002, Morrow, et al, 1999, Yan and Wang, 1998 Several transcription factors are clearly essential for photoreceptor development, and their mutations cause retinal degenerations: NRL, CRX, Otx2, Trβ2 (thyroid hormone receptor β2), and NR2E3. (Bessant, et al, 1999, DeAngelis, et al, 2002, Freund, et al, 1997, Haider, et al, 2000, Haider, et al, 2001, Martinez-Gimeno, et al, 2001, Ng, et al, 2001, Nishida, et al, 2003, Swain, et al, 1997 However, our knowledge of the interactions of these cell-specific proteins with each other and upstream signal transduction proteins remains sparse.…”
Section: Introductionmentioning
confidence: 99%
“…(Carl, et al, 2002, Mathers and Jamrich, 2000, Porter, et al, 1997 The bHLH (basic Helix Loop Helix) gene family of transcription factors also has pivotal roles in the unique patterning of transcription factors that guide retinal development (Mash1, Math3, Ngn2). (Akagi, et al, 2004, Brown, et al, 1998, Brown, et al, 2001, Hojo, et al, 2000, Kanekar, et al, 1997, Marquardt and Gruss, 2002, Moore, et al, 2002, Morrow, et al, 1999, Yan and Wang, 1998 Several transcription factors are clearly essential for photoreceptor development, and their mutations cause retinal degenerations: NRL, CRX, Otx2, Trβ2 (thyroid hormone receptor β2), and NR2E3. (Bessant, et al, 1999, DeAngelis, et al, 2002, Freund, et al, 1997, Haider, et al, 2000, Haider, et al, 2001, Martinez-Gimeno, et al, 2001, Ng, et al, 2001, Nishida, et al, 2003, Swain, et al, 1997 However, our knowledge of the interactions of these cell-specific proteins with each other and upstream signal transduction proteins remains sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, NeuroD may not have been active in all of the transfected cells. Recent data in the developing frog retina has indicated that the neurogenic activity of NeuroD is modulated by phosphorylation by GSK3␤ (Moore et al, 2002). Because phosphorylation suppresses the neurogenic activity of NeuroD in amphibians (Moore et al, 2002), it is possible that transfected NeuroD may be inactive in progenitors derived from postnatal chick retina by GSK-like enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data in the developing frog retina has indicated that the neurogenic activity of NeuroD is modulated by phosphorylation by GSK3␤ (Moore et al, 2002). Because phosphorylation suppresses the neurogenic activity of NeuroD in amphibians (Moore et al, 2002), it is possible that transfected NeuroD may be inactive in progenitors derived from postnatal chick retina by GSK-like enzymes. It is also possible that some of the proliferating cells derived from damaged retinas express high levels of bHLH factors that may compete for binding at E-box sites in promoting regions of genes or somehow inhibit the neurogenic activity of NeuroD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ohnuma et al (Ohnuma et al, 2002) have recently shown that when Xenopus Xath5 is misexpressed in RPCs together with factors enhancing proliferation, it no longer promotes ganglion cell fate but favours later retinal fates. Similarly, when Ath5 is misexpressed in late RPCs both in Xenopus and in chick, its ability to promote early cell fates decreases (Matter-Sadzinski et al, 2001;Moore et al, 2002). Finally, the neurogenic gene Notch regulates the ability of Xath5 to promote ganglion cell differentiation, by modulating in time and space the relative levels of Xath5 activity in the retinal precursors (Moore et al, 2002;Ohnuma et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, when Ath5 is misexpressed in late RPCs both in Xenopus and in chick, its ability to promote early cell fates decreases (Matter-Sadzinski et al, 2001;Moore et al, 2002). Finally, the neurogenic gene Notch regulates the ability of Xath5 to promote ganglion cell differentiation, by modulating in time and space the relative levels of Xath5 activity in the retinal precursors (Moore et al, 2002;Ohnuma et al, 2002). These data altogether strongly suggest that additional factors are required for proper specification of ganglion cell fate (reviewed by Vetter and Brown, 2001).…”
Section: Introductionmentioning
confidence: 99%